Production of copropophyrin III, biliverdin and bilirubin by the rufomycin producer, Streptomyces atratus - Perez-Ortiz, Gustavo; Sidda, John D.; Peate, Jessica; Ciccarelli, Davide; Ding, Yaoyu; Barry, Sarah M. (Frontiers in Microbiology, 2023)
Heme is best known for its role as a versatile prosthetic group found in prokaryotic and eukaryotic proteins with diverse biological functions including gas and electron transport, as well as a wide array of redox chemistry. However, free heme and related tetrapyrroles also have important roles in the cell. In several bacterial strains, heme biosynthetic precursors and degradation products have been proposed to function as signaling molecules, ion chelators, antioxidants and photoprotectants. While the uptake and degradation of heme by bacterial pathogens is well studied, less is understood about the physiological role of these processes and their products in non-pathogenic bacteria. Streptomyces are slow growing soil bacteria known for their extraordinary capacity to produce complex secondary metabolites, particularly many clinically used antibiotics. Here we report the unambiguous identification of three tetrapyrrole metabolites from heme metabolism, coproporphyrin III, biliverdin and bilirubin, in culture extracts of the rufomycin antibiotic producing Streptomyces atratus DSM41673. We propose that biliverdin and bilirubin may combat oxidative stress induced by nitric oxide production during rufomycin biosynthesis, and indicate the genes involved in their production. This is, to our knowledge, the first report of the production of all three of these tetrapyrroles by a Streptomycete.